Supercritical fluid chromatography in pharmaceutical analysis - Desfontaine, Vincent; Guillarme, Davy; Francotte, Eric; Nováková, Lucie (Journal of pharmaceutical and biomedical analysis, 2015)
In the last few years, there has been a resurgence of supercritical fluid chromatography (SFC), which has been stimulated by the introduction of a new generation of instruments and columns from the main providers of chromatographic instrumentation, that are strongly committed to advancing the technology. The known limitations of SFC, such as weak UV sensitivity, limited reliability and poor quantitative performance have been mostly tackled with these advanced instruments. In addition, due to the obvious benefits of SFC in terms of kinetic performance and its complementarity to LC, advanced packed-column SFC represents today an additional strategy in the toolbox of the analytical scientist, which may be particularly interesting in pharmaceutical analysis. In the present review, the instrumentation and experimental conditions (i.e. stationary phase chemistry and dimensions, mobile phase nature, pressure and temperature) to perform "advanced SFC" are discussed. The applicability of SFC in pharmaceutical analysis, including the determination of drugs in formulations and biofluids is critically discussed.
Keywords: léčivé přípravky; Chromatography, Supercritical Fluid; Pharmaceutical Preparations; Chemistry, Pharmaceutical; farmaceutická chemie; superkritická fluidní chromatografie